Pengaruh Intellectual Capital Terhadap Kinerja Keuangan Dengan Competitive Advantage Sebagai Variabel Moderating - Ayu Khodijah Ida Kusuma; Suwandi Suwandi (Universitas Muhammadiyah Gresik, 2022)
This study aims to analyze the effect of intellectual capital on financial performance in consumer goods manufacturing companies with competitive advantage as a moderating variable. The population in this study are manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange during the period 2018 to 2020 using the company's annual financial statements taken through the purposive sampling method and based on predetermined criteria in order to obtain 42 consumer goods manufacturing companies that meet the criteria. criteria. The sampling criteria selected were 1) manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange during the period 2018 – 2020. 2) Manufacturing companies in the consumer goods sector that publish their finances in full and in rupiah during the period 2018 – 2020. 3 ) Manufacturing companies in the consumer goods sector that have complete data needed in the research period 2018 - 2020. The data analysis technique used is Partical Least Square (PLS) with SmartPLS 3.0 data processing The results of this study show that: 1) Intellectual Capital has an effect on financial performance. 2) Competitive Advantage has no effect on financial performance. 3) Competitive Advantage can moderate the relationship between intellectual capital and financial performance.